Australian women educators’ internal exile and banishment in a centralised patriarchal state school system - Whitehead, Kay (Historia y Memoria de la Educación, 2022)
This article explores Australian women teachers’ struggles for equality with men from the late nineteenth to the mid-twentieth century. While Australia purported to be a progressive democratic nation, centralised patriarchal state school systems relied on women teachers to fulfil the requirements of free, compulsory and secular schooling. This study focuses on the state of South Australia where women were enfranchised in 1894, far ahead of European countries. However, women teachers were subjected to internal exile in the state school system, and banished by the marriage bar. The article begins with the construction of the South Australian state school system in the late nineteenth century. The enforcement of the marriage bar created a differentiated profession of many young single women who taught prior to marriage; a few married women who required an income; and a cohort of senior single women who made teaching a life-long career and contested other forms of subordination to which all women teachers were subject. Led by the latter group, South Australian women teachers pursued equality in early twentieth century mixed teachers unions and post-suffrage women’s organisations; and established the Women Teachers Guild in 1937 to secure more equal conditions of employment. The paper concludes with the situation after World War Two when married women were re admitted to the state school system to resolve teacher shortages; and campaigns for equal pay gathered momentum. In South Australia, the marriage bar was eventually removed in 1972.